S100A4-lineage cells contribute modestly to angiotensin II-mediated thoracic aortic aneurysms through angiotensin II type 1a receptor in mice - Sohei Ito; Jeff Z. Chen; Deborah A. Howatt; Jessica J. Moorleghen; Hong S. Lu; Alan Daugherty; Hisashi Sawada (PLoS ONE, 2026)
Angiotensin II (AngII) exerts a critical role in thoracic aortic aneurysm (TAA) formation via AngII type 1a receptor (AT1aR). However, the principal cell type mediating this process remains unclear. Our previous study demonstrated that S100A4-lineage cells are present in the aortic wall and involved in AngII-induced vascular remodeling. In the present study, we investigated whether S100A4-lineage cells contribute to AngII-mediated TAA formation through AT1aR. Proteomic, bulk RNA sequencing, and single-cell RNA sequencing data were analyzed to assess changes in S100A4 abundance in response to AngII infusion. Lineage tracing was performed to track S100A4-lineage cells during AngII-mediated TAA formation. Either saline or AngII was infused in mice with genetic deletion of AT1aR in S100A4-lineage cells and their wild-type littermates. AngII infusion increased S100A4 protein and mRNA abundance significantly in the ascending aorta, particularly within smooth muscle cells and fibroblasts. Lineage tracing revealed that S100A4-positive cells were localized to the media and adventitia under basal conditions. Following AngII infusion, S100A4-lineage cells expanded markedly throughout the entire aortic wall and comprised a heterogeneous population including smooth muscle cells and fibroblasts. Deletion of AT1aR in S100A4-lineage cells partially reduced AngII-induced TAA formation. In conclusion, S100A4-lineage cells modestly contribute to AngII-mediated TAA development through AT1aR in mice.